Recent Trends in Computational Science and Engineering - Serdar Çelebi, M. (IntechOpen, 2018)
Computational science and engineering (CSE) is a broad multidisciplinary and integrative area including a variety of applications in science, engineering, numerical methods, applied mathematics, and computer science disciplines. The book covers a collection of different types of applications and visions to various disciplinary key aspects, which comprises both problem-driven and methodology-driven approaches at the same time. These selected applications are: Computational and information technologies for numerical models and large unstructured data processing Evolution of matrix computations and new concepts in computing Inverse problems covering both classical and newer approaches Integro-differential scheme (IDS) that combines finite volume and finite difference methods Smart city wireless networks Signal processing methods